Exploring blind spots in collaborative value creation in building design: a creativity perspective. Issue 4 (2nd October 2021) - Biskjaer, Michael Mose; Kamari, Aliakbar; Jensen, Stina Rask; Kirkegaard, Poul Henning
ABSTRACT: Defining, developing, and delivering value is critical in integrated design processes (IDP) in building design and its two core design disciplines, architectural design and engineering design. Even so, how values emerge—the creation part itself—is underexposed. Using the seminal four p model from creativity research (person, process, product, and press) as an analytical lens, the paper explores blind spots in two building design cases that we as architects and researchers in creativity and engineering design have been involved in. On this basis, the paper contributes a four-leaf clover model of potential blind spots in collaborative value creation in building design. The model is comprised of value exploration, value negotiation, value formulation, and value manifestation . Design researchers can use the model as a scaffold for new design value theory, and design practitioners can employ it as an instrument to better navigate collaborative building design processes with multiple stakeholders, whose individual value sets may not always be clearly articulated and hence may sometimes collide.